Peningkatan Kemampuan Menulis Teks Prosedur Menggunakan Model Project Based Learning Siswa Kelas VII-3 SMPN 45 Medan - Fathiah Riadianti; Wulan Nurhasanah; Futi Hamdiyah Telaumbanua; Khadavi Khadavi; Mustika Wati Siregar (CV. Alim's Publishing, 2024)
This type of research is Classroom Action Research (PTK). The subjects in this research were in class VII-3 with a total of 30 students. The aim of this research is to improve the learning quality of class VII-3 students at SMPn 45 Medan in procedural texts using the project based learning model. The project based learning model is a model that involves a project in the learning process. Based on research, the application of the project based learning model is very effective because students' results of writing procedural texts have increased from cycle I to cycle II.